The Dorsomedial Hypothalamus Is Involved in the Mediation of Autonomic and Neuroendocrine Responses to Restraint Stress - Taíz F. S. Brasil; Silvana Lopes-Azevedo; Ivaldo J. A. Belém-Filho; Eduardo A. T. Fortaleza; José Antunes-Rodrigues; Fernando M. A. Corrêa (Frontiers Media S.A., 2020)
We hypothesized that dorsomedial hypothalamus (DMH) modulates autonomic and neuroendocrine responses in rats at rest and when subjected to restraint stress (RS). Male Wistar rats were used, and guide cannulas were bilaterally implanted in the DMH for microinjection of vehicle or the nonspecific synaptic blocker CoCl2 (1 mM/100 nl). A polyethylene catheter was inserted into the femoral artery for the recording of arterial pressure and heart rate (HR). Tail temperature was measured using a thermal camera. The session of RS started 10 min after DMH treatment with vehicle or CoCl2. Under home-cage condition, the pretreatment of DMH with CoCl2 increased baseline blood pressure (BP), and heart rate (HR) without affecting the tail temperature. In addition, it decreased plasma vasopressin levels without affecting plasma corticosterone and oxytocin contents. When rats pretreated with CoCl2 were exposed to RS, the RS-evoked cardiovascular were similar to those observed in vehicle-treated animals; however, because cobalt pretreatment of the DMH increased baseline BP and HR values, and the RS-evoked cardiovascular responses did not exceed those observed in vehicle-treated animals, suggesting a possible celling limit, the possibility that DMH is involved in the modulation of RS-evoked cardiovascular responses cannot be certainly excluded. Nonetheless, the pretreatment of DMH with CoCl2 blocked the reduction in tail temperature caused by RS. The DMH pretreatment with CoCl2 did not modify the RS-evoked increase in plasma corticosterone and oxytocin contents. In conclusion, the present data suggest the involvement of DMH in the maintenance of BP, HR, and vasopressin release under the rest conditions at the home-cage. Furthermore, indicate that DMH is an important thermoregulatory center during exposure to RS, regulating tail artery vasoconstriction.